Facility Assessment and Accreditation Trends in Indonesian Madrasah Aliyah: Opportunities for Enhancing Educational Infrastructure - Refina Refina; R. Madhakomala (Interdisciplinary Journal of Advanced Research and Innovation, 2024)
This study analyzes Madrasah Aliyah (MA) accreditation in Indonesia, drawing upon data sourced from the Ministry of Religion. The results illuminate optimistic trends, showcasing substantial proportions of MAs achieving Accreditation B (51%) and Accreditation A (43.9%). Notably, regional variations accentuate diverse educational priorities, with private MAs consistently outpacing their public counterparts in accreditation levels. Despite overall alignment with infrastructure standards, it is imperative to address the 26% of MAs with Accreditation C and the 1% lacking accreditation. The strategic distribution of laboratories and facilities underscores a resolute commitment to providing comprehensive learning experiences. In conclusion, Indonesia’s MA system has attained commendable achievements, yet there exists a pressing need for concentrated efforts to rectify regional disparities, enhance public school accreditation, and elevate facility quality, thereby enriching the overall educational landscape. A call for continuous monitoring and targeted interventions is sounded, urging stakeholders to actively engage in sustained improvement initiatives. Through such dedicated endeavors, the Indonesian MA system can fortify its foundations and uphold its commitment to delivering quality education across diverse regions.